Examining American and Chinese Students’ Strategies When Giving Face-to-Face Critical Feedback in Academic Settings - Chau, Nguyen (Journal of Asia TEFL, 2018)
While the literature on popular Face Threatening Acts (FTAs) such as complaining, requesting, promising, apologizing, and giving and receiving compliments is thriving, the speech act of giving critical feedback in an intercultural setting is quite understudied (but see Itakura & Tsui, 2011; Nguyen, 2008, 2012). In addressing this issue, this paper aims at examining how American and Asian students utilize mitigating strategies when giving face-to-face critical feedback. The study was also designed to record these students' strategy modification in order to adapt to an intensified level of face-threat. Ten participants (five American and five Chinese students) were recruited to join a three-part interview. For the first component of the study, the subjects watched a video of a badly presented presentation and played the role of the presenter's classmates to comment on the presenter's presenting skill (Task A). The face-threatening level was then enhanced as the interviewees were required to imagine facing and giving feedback directly to the presenters (Task B). The second step features the participants reading four written arguments and making critical evaluations (Task C). The change in face-threatening level was marked when the participants' comments were unexpectedly challenged by the interviewer who pretended to hold an opposite viewpoint (Task D). Finally, a semi-structured interview was carried out to find out the participants' perspectives on giving critical feedback. Collected data reveal fairly equivalent use of mitigating devices by American and Chinese students in Task A and C, while some divergences in strategies were observed in Task B and D.